Improving China’s regional financial center modernization development using a new hybrid MADM model - Hu, Kuang-Hua; Jianguo, Wei; Tzeng, Gwo-Hshiung (Technological and Economic Development of Economy, 2018)
The regional financial center is the propeller of regional economic development. Regional financial center modernization, however, has been the predominant propulsion of economic sustainability. Decisions related to regional financial center modernization development are inherent problems of multiple attribute decision-making (MADM), and strategically important to the government. The purpose of this paper is to set up a regional financial center improvement model for modernization development, as based on a hybrid MADM model, which addresses the main causal-effect factors and amended priorities in order to strengthen ongoing planning. This paper adopts a new hybrid MADM model combined with the DEMATEL technique to construct an influential network relationship map (INRM) and determined the influential weights of DANP. Then, a modified VIKOR method using influential weights is applied to measure and integrate the performance gaps from each criterion into dimensions, as well as the overall criterion for evaluating and improving the modernization development of the regional financial center, as based on INRM. Finally an empirical case study using data from the Guangzhou regional financial center is carried out as an example to demonstrate the suitability of the proposed hybrid MADM model for solving real-world problems. The results show the priorities for improvement, as based on the degree of the effect and impact of the dimensions, as follows: first is making “government policy”, second is enforcing “financial infrastructure and safety”, next is formulating “financial institutions and human resources”, and finally “financial service”.First published online: 22 Mar 2017